Moderating role of political connection on financial distress and earnings management - Sambuaga, Elfina Astrella (Jurnal Ekonomi Modernisasi, 2023)
This study aims to examine the effect of financial distress and political connections on earnings management and the role of both accrual and real earnings management behavior. This study's detection of financial distress uses two proxies. The sample of this study uses non-financial and real estate companies listed on the Indonesia Stock Exchange with 916 observations. The findings show that financial distress significantly affects accrual earnings management behavior, but no evidence supports its effect on real earnings management. Furthermore, political connections are also not proven to affect earnings management. However, companies in financial distress with political connections will be more aggressive in performing real earnings management.